Prevalence of Posttraumatic Stress Disorder among Breast Cancer Patients: A Meta-analysis - Wu, Xin; Wang, Jieru; Cofie, Reuben; Kaminga, Atipatsa C.; Liu, Aizhong (Tehran University of Medical Sciences, 2016)
BACKGROUND: Prevalence estimates of Posttraumatic Stress Disorder (PTSD) among breast cancer pa-tients varied widely in existing studies. This study aimed to provide an overall prevalence estimate of PTSD among breast cancer patients, and the prevalence estimates related to specific PTSD diagnosis tools. METHODS: Systematic search of relevant articles was made from seven databases. Freeman-Tukey Dou-ble Arcsine Transformation was used to estimate the overall prevalence of PTSD. Sub-group and meta-regression analyses were used to investigate the between-study sources of heterogeneity. Publication bias was examined using Egger’s funnel plot and Begg test. RESULTS: The pooled prevalence of PTSD among breast cancer patients was [9.6%, 95% confidence in-tervals (95%CI)=7.9-11.5%]. Studies that used Clinician Administered PTSD Scale-Form (CAPS) method alone yielded much higher prevalence (19.0%, 95%CI=13.1-25.5%, n=5) than three or fourth edition Structured Clinical Interview for Diagnostic and Statistical Manual (SCID) method alone (3.0%, 95%CI= 2.2-3.9%, n=11). Prevalence estimates for studies that used the methods: PTSD Checklist—Civilian Version (PCL-C) cut-off, PCL-C cluster, and Impact of Event Scale (IES) cut-off were (7.0%, 95%CI= 3.9-10.8%, n=10), (11.5%, 95%CI= 8.6-15.6%, n=11) and (15.1%, 95%CI= 12.3-18.2%, n=4), respectively. Heterogeneity between-study was substantial (I2=44.9–92.3%). CONCLUSION: About 9.6% of the breast cancer patients would develop the PTSD symptoms. Those who were younger, non-Caucasian and recently completed treatment would be at a greater risk of developing PTSD.
Keywords: Posttraumatic stress disorder; Breast cancer; Prevalence; Meta-analysis